Metal forming beyond shaping: Predicting and setting product properties. Issue 2 (2015) - Tekkaya, A.E.; Allwood, J.M.; Bariani, P.F.; Bruschi, S.; Cao, J.; Gramlich, S.; Groche, P.; Hirt, G.; Ishikawa, T.; Löbbe, C.; Lueg-Althoff, J.; Merklein, M.; et al.
Abstract Metal forming is not only shaping the form of a product, it is also influencing its mechanical and physical properties over its entire volume. Advanced analysis methods recently enable accurate prediction of these properties and allow for setting these properties deterministically during the forming process. Effective measurement methods ensure the setting of these predicted properties. Several real examples demonstrate the impressive achievements and indicate the necessity of a paradigm change in designing products by including manufacturing-induced effects in the initial dimensioning. This paradigm change will lead to lightweight components and serve environmentally benign designs.